Effective techniques for developing advanced vocabulary skills in English language - Yu. Kovalenko (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The present paper is dedicated to developing advanced vocabulary skills in English. Mastering vocabulary is paramount for English language learners who strive for fluent and accurate communication. This article examines the importance of advanced vocabulary skills for language acquisition and the challenges of students’ vocabulary development. Based on current research results from prominent scientists, the article summarizes insights into effective techniques for developing advanced vocabulary skills. The study highlights the diverse role of vocabulary in language mastery and its impact on academic and professional success. It highlights the importance of tailored strategies for vocabulary teaching, including contextual learning, semantic mapping, morphological awareness, incidental learning, and vocabulary games and activities. Additionally, the article examines cutting-edge technology-enhanced vocabulary learning strategies, such as online resources, mobile applications, and adaptive learning platforms, designed to improve students’ vocabulary proficiency. Through a comprehensive review of the literature and analysis of current research, the article explains the challenges of vocabulary acquisition and the need for further investigation of its dimensions, reasons, and consequences. It emphasizes the need for educators to employ effective techniques that facilitate the development of advanced vocabulary skills in English language students. In summary, recognizing the importance of vocabulary in language acquisition and adopting innovative strategies for vocabulary development are essential steps to enable students to realize the full potential of language, promote academic and professional excellence, and embark on a journey of lifelong learning and personal growth.